PENENTUAN ARSIP VITAL MELALUI KEGIATAN IDENTIFIKASI ARSIP VITAL PADA ARSIP NASIONAL REPUBLIK INDONESIA TAHUN 2019: Array - Lufi Herawan (Jurnal Kearsipan, 2020)
Vital records program is a mandate of the Law of the Republic of Indonesia Number 43 of 2009 that state institutions and government agencies must implement, both central and regional, including ANRI. The purpose of organizing this vital records program is to protect, secure and save the very important records. Vital records program must be supported by establishing a vital records regulation in a form of a list as a reference for managing vital records. ANRI as a non-ministerial government institution has not established the regulation about vital records yet, so there are still many obstacles in implementing the vital records program. This research is a descriptive study. This study aims to determine vital records in the ANRI environment using the method of applying the Head of ANRI Regulation Number 6 of 2005. The determination of records criteria is based on that regulation and criteria from NARA, while the stages used are the stages listed in that regulation. Implementing this study concluded that 18 work units got 11 work units that had vital records, with 20 types of vital records.